2023
DOI: 10.1097/anc.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of the Impact of NICU Visitation Policies and Restrictions Due to the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has impacted parents' ability to participate in their infants' care during the neonatal intensive care unit (NICU) stay in unprecedented ways. Purpose: The purpose of this study was to explore the lived experience of parents whose infants was in the NICU during the COVID-19 pandemic. Methods: A qualitative telephone interview survey was conducted. Participants included paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, restrictions during the COVID-19 era have often made this impossible. It is already described that, during the pandemic period, parents experienced increased stress due to the restricted NICU visitation policies, limited opportunities to care for their infant, lack of support, and inconsistent communication regarding their infant status and COVID-19 protocols [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, restrictions during the COVID-19 era have often made this impossible. It is already described that, during the pandemic period, parents experienced increased stress due to the restricted NICU visitation policies, limited opportunities to care for their infant, lack of support, and inconsistent communication regarding their infant status and COVID-19 protocols [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, restrictions during the COVID-19 era often made this not possible. It is already described that, during pandemic period, parents experienced increased stress due to the restricted NICU visitation policies, limited opportunities to care for their infant, lack of support, and inconsistent communication regarding their infant status and COVID-19 protocols [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yance and colleagues further describe the experiences of mothers in Ontario, Canada. 8 Parental presence early in the pandemic was limited to one parent for a scheduled 3-hour period of time. Mothers reported that building trust with the healthcare team during those uncertain times was essential.…”
mentioning
confidence: 99%